PENGARUH METODE TUTOR SEBAYA TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Valeria Gisda Dwata; Hamdani Hamdani; Siti Halidjah (Universitas Tanjungpura, 2019)
AbstractThis study aimed was to analyze the influence peer tutoring method of student learning output in learning mathematics in grade V of State Elementary School 06 North Pontianak. the research method was an experiment, form of quasi Experimental's non-equivalent group design. the research population of all grade V students of public Elementary School 06 North Pontianak werw counted to 43 students. the withdrawal sample tec hnique used purposive sample. the technique used was observation and measuring. the data collection tools are observation sheets and essay question. the data result was the average score of class control post-test was 62,09 and the experiment was 70.69. based on the counting result t-test was 2,060 > t-table 2,020 then ha is accepted. it shows that there is a difference in students learning output of class control and class experiment. the value of effect size was 0,77 with middle criteria. it can conclusion that there is an effect of the application of the peer tutoring method on student learning output in learning mathematics in grade V public Elementary School 06 North Pontianak.Keywords: Learning Outcomes,Mathematics, Peer Tutoring